2018
DOI: 10.1371/journal.pone.0202780
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and tissue-specific proteolytic processing of chemerin in obese mice

Abstract: Chemerin is a chemoattractant involved in immunity as well as an adipokine, whose activity is regulated by successive proteolytic cleavages at its C-terminus. Chemerin’s C-terminal sequence and its proteolytic cleavage sites are highly conserved between human and mouse, as well as in other species. We produced, purified and characterized different mouse chemerin forms. Ca2+ mobilization assay showed that the EC50 values for mchem161T and mchem157R were 135.8 ± 158 nM and 71.2 ± 55.4 nM, respectively, whereas m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…Murine chemerin-156 and chemerin-155 are both highly active isoforms [27]. In the present study, chemerin-155 was the most abundant variant found in tumor tissues, whereas chemerin-156 was not detected.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Murine chemerin-156 and chemerin-155 are both highly active isoforms [27]. In the present study, chemerin-155 was the most abundant variant found in tumor tissues, whereas chemerin-156 was not detected.…”
Section: Discussionsupporting
confidence: 45%
“…In the present study, chemerin-155 was the most abundant variant found in tumor tissues, whereas chemerin-156 was not detected. Chemerin-154 and chemerin-153, which are believed to be biologically inactive [27], were the two other isoforms found in liver cancers. Chemerin-153 was more abundant in the tumors of mice with chemerin-156 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations